Methionine Deficiency Affects Liver and Kidney Health, Oxidative Stress, and Ileum Mucosal Immunity in Broilers - Song, Baolin; Fu, Min; He, Fang; Zhao, Huan; Wang, Yu; Nie, Qihang; Wu, Bangyuan (Frontiers in Veterinary Science, 2021)
Methionine (Met) is the first limiting amino acid in broiler diets, but its unclear physiological effects hamper its effective use in the poultry production industry. This study assessed the effect of a Met-deficient (MD) diet on chicken liver and kidney health, exploring the associated mechanisms of antioxidant capacity and ileum mucosal immunity. Seventy-two broilers were administered either the control diet (0.46% Met in starter diet, 0.36% Met in grower diet) or the MD diet (0.22% Met in starter diet, 0.24% Met in grower diet). Liver and kidney samples were collected every 14 days for anatomical, histological, and ultrastructural analyses, accompanied by oxidative stress assessment. Meanwhile, T- and B-lymphocyte abundance and essential cytokine gene expression were measured in the ileum, the center of the gut–liver–kidney axis. Signs of kidney and liver injury were observed morphologically in the MD group at 42 days of age. Furthermore, aspartate aminotransferase, alanine aminotransferase, creatinine, and uric acid levels were decreased in the MD group compared with the control group, accompanied by decreased superoxide dismutase activity, increased malondialdehyde content, decreased numbers of T and B lymphocytes, and decreased cytokine expression in the ileum, such as IL-2, IL-6, LITAF, and IFN-γ. These results suggest that MD can induce kidney and liver injury, and the injury pathway might be related to oxidative stress and intestinal immunosuppression.